Top 50 medical journals from Balkan countries: A bibliometric analysis, 2000–2020 - Okan Aydoğan; Gizem Kayan-Tekaüt (European Science Editing)
Background: Science Citation Index Expanded (SCIE) is one of the most important indexes that medical journals aspire to be covered by. Currently, SCIE indexes 14,840 peer-reviewed journals across 178 disciplines. Among these journals are 3445 medical journals, divided into more than 40 subject categories.Objectives: To reveal the impact and contribution of medical journals from Balkan countries through the Journal Impact Factor of those journals, the number of articles published by them, and the number of times those articles have been cited.Methods: Balkan countries are countries that fall or fully or partly within the Balkan peninsula. All medical journals from those countries listed in the SCIE were ranked based on cumulative citations between 2000 and 2020. Among them, the top 50 journals in terms of cumulative citations were chosen for the study, which analysed the data on 129,259 research articles and reviews that covered 27 different subject categories within the broad field of medicine. The countries were Bosnia & Herzegovina, Croatia, Greece, North Macedonia, Romania, Serbia, Slovenia, and TurkeyResults: The top 50 journals included those published from eight Balkan countries. Turkey had the most journals (21) in the Web of Science (WoS) and Greece had 13 but, when ranked in terms of the number of journals in WoS per million people, Croatia topped the list, with 1.22 journals per million of its population, followed by Greece (1.21 journals). The top-cited journals were Anticancer Research (206,226 citations), International Journal of Oncology (171,654), Oncology Reports (157,467), Molecular Medicine Reports (82,009), and Oncology Letters (69,161). Oncology was the most cited subject category and Croatia, the country with maximum interaction with other Balkan countries, that is, papers in Croatian journals cited journals published from the maximum number of Balkan counties.Conclusion: The study provides insights into the last two decades of progress in academic publishing and in the performances of medical journals published from Balkan countries.